Novel Molecular Markers Linked to Pseudomonas aeruginosa Epidemic High-Risk Clones - Wedad Nageeb; Dina H. Amin; Zuhair M. Mohammedsaleh; Rabab R. Makharita (MDPI AG, 2021)
The population structure of Pseudomonas aeruginosa is panmictic-epidemic in nature, with the prevalence of some high-risk clones. These clones are often linked to virulence, antibiotic resistance, and more morbidity. The clonal success of these lineages has been linked to acquisition and spread of mobile genetic elements. The main aim of the study was to explore other molecular markers that explain their global success. A comprehensive set of 528 completely sequenced P. aeruginosa genomes was analyzed. The population structure was examined using Multilocus Sequence Typing (MLST). Strain relationships analysis and diversity analysis were performed using the geoBURST Full Minimum Spanning Tree (MST) algorithm and hierarchical clustering. A phylogenetic tree was constructed using the Unweighted Pair Group Method with Arithmetic mean (UPGMA) algorithm. A panel of previously investigated resistance markers were examined for their link to high-risk clones. A novel panel of molecular markers has been identified in relation to risky clones including armR, ampR, nalC, nalD, mexZ, mexS, gyrAT83I, gyrAD87N, nalCE153Q, nalCS46A, parCS87W, parCS87L, ampRG283E, ampRM288R, pmrALeu71Arg, pmrBGly423Cys, nuoGA890T, pstBE89Q, phoQY85F, arnAA170T, arnDG206C, and gidBE186A. In addition to mobile genetic elements, chromosomal variants in membrane proteins and efflux pump regulators can play an important role in the success of high-risk clones. Finding risk-associated markers during molecular surveillance necessitates applying more infection-control precautions.